HUBUNGAN ASUPAN ENERGI, PROTEIN, STATUS GIZI, DAN SUHU LINGKUNGAN DENGAN PRODUKTIVITAS KERJA (Studi Pada Para Pekerja CV. Industri Plastik Babatan Ungaran, Kabupaten Semarang Tahun 2018) - Safina Andita Dewi; Dina Rahayuning Pangestuti; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Work nutrition is a nutrition applied to employees to meet their needs in accordance with the type and workplace with the aim of improving efficiency and productivity as high as possible. Work productivity is the comparison between the results achieved with the role of labor unity time. The purpose of this study was to determine the relationship between energy, protein, liquid, nutrition status and enviromental temperature with work productivity. The type of this research was quantitative with cross sectional design. The population of the research was all worker on CV. Plastic Industries, Babatan Ungaran, Semarang District. Sampling technique was total sampling of 46 workers on CV. Plastic Industries, Babatan Ungaran, Semarang District in 2018. Anthropometric measurements were conducted in body weight, height and body fat, characteristic questionnaire filling, Semi Quantitative Food Frequency Questionnaires (FFQ), measured the temperature and humidity of the room. The data analysis used rank spearman test. After doing the research, the result showed that there was a relation between energy (p=0,00), protein (p=0,03), Body Mass Index (p=0,00) and body fat (p=0,00) with work productivity on CV. Plastic Industries, Babatan Ungaran, Semarang District in 2018. There was no relation of liquid (p=0,26) and enviromental temperature (p=0,27) ) with work productivity on CV. Plastic Industries, Babatan Ungaran, Semarang District in 2018. It was suggested for employees is apply a healthy lifestyle by eating a balanced diet and do routine physical activity and the need for increased fluid intake.